Energy Drinks - the potential risk to the cardiovascular system. A Review - Piwowar, Michalina; Agopsowicz, Katarzyna; Blicharz, Katarzyna; Zdziebło, Piotr; Sitko, Maria; Biernacka, Martyna; Stolarczyk, Dominika; Bąk, Aleksandra; Mojżesz, Piotr; Biernacki, Igor (Journal of Education, Health and Sport, 2025)
Energy drinks are products that have gained popularity in recent years among people seeking a quick energy boost. The ingredients they contain are intended to reduce the feeling of fatigue, improve the body's performance and concentration. The consumption of energy drinks raises controversy due to their potential negative impact on health, particularly on the cardiovascular system. Thanks to the increased interest of scientists in this topic, many reports of cardiovascular events related to the consumption of energy drinks have been created. This article discusses the composition of energy drinks their association with arrhythmias, hypertension, myocardial infarction, and coronary vasospasm., as well as examples of adverse events that occurred after their consumption.While further research is necessary to fully understand the long-term cardiovascular outcomes, this review highlights the importance of public awareness and regulatory measures to mitigate potential health risks associated with energy drink use.